New Insights into Aspirin’s Anticancer Activity: The Predominant Role of Its Iron-Chelating Antioxidant Metabolites - George J. Kontoghiorghes (Antioxidants)
Epidemiological studies have suggested that following long-term, low-dose daily aspirin (LTLDA) administration for more than 5 years at 75–100 mg/day, 20–30% of patients (50–80 years old) had a lower risk of developing colorectal cancer (CRC) and about the same proportion in developing iron deficiency anemia (IDA). In cases of IDA, an increase in iron excretion is suspected, which is caused by aspirin chelating metabolites (ACMs): salicylic acid, salicyluric acid, 2,5-dihydroxybenzoic acid, and 2,3-dihydroxybenzoic acid. The ACMs constitute 70% of the administered aspirin dose and have much longer half-lives than aspirin in blood and tissues. The mechanisms of cancer risk reduction in LTLDA users is likely due to the ACM’s targeting of iron involved in free radical damage, iron-containing toxins, iron proteins, and associated metabolic pathways such as ferroptosis. The ACMs from non-absorbed aspirin (about 30%) may also mitigate the toxicity of heme and nitroso-heme and other iron toxins from food, which are responsible for the cause of colorectal cancer. The mode of action of aspirin as a chelating antioxidant pro-drug of the ACMs, with continuous presence in LTLDA users, increases the prospect for prophylaxis in cancer and other diseases. It is suggested that the anticancer effects of aspirin depend primarily on the iron-chelating antioxidant activity of the ACMs. The role of aspirin in cancer and other diseases is incomplete without considering its rapid biotransformation and the longer half-life of the ACMs.